2007
DOI: 10.1177/0091270007302564
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/Ritonavir Pharmacokinetic Profile: Impact of Sex and Other Covariates Following a Change From Twice‐Daily to Once‐Daily Therapy

Abstract: The aim of this study was to determine the impact of sex on the pharmacokinetics of lopinavir/ ritonavir. Interaction between lopinavir/ritonavir and tenofovir was also evaluated. Steady-state plasma samples were obtained from virologically suppressed HIV-infected patients on lopinavir/ ritonavir 800/200-mg soft gel capsule taken once daily. Drug assays were performed by highperformance liquid chromatography. Pharmacokinetic parameters estimated by noncompartmental method were reported as 90% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Total LPV (LPV t ) and RTV were measured by high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection [8]. Free LPV (LPV f ) was quantitated using equilibrium dialysis followed by mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Total LPV (LPV t ) and RTV were measured by high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection [8]. Free LPV (LPV f ) was quantitated using equilibrium dialysis followed by mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…HIV PIs, for example, are generally highly, but variably, bound to AAG, thereby affecting the unbound (or active) concentration of the drug in plasma and tissues (Delille et al 2014). Some studies have noted higher plasma concentrations of certain PIs in women compared with men (Pai et al 2004;Fletcher et al 2004), but not others (Ofotokun et al 2007a). However, one study noted that changes in plasma AAG levels altered total but not free concentrations or the antiviral activity of the PI lopinavir (Ofotokun et al 2011), suggesting that sex-related changes in AAG may not affect a drug's pharmacodynamics effect.…”
Section: Distributionmentioning
confidence: 99%
“…13 Difference in patient gender has not been found to have an effect on LPV/r concentrations. 14 Exposure to LPV/r has been found to be lower in the third trimester of pregnancy, but further research has found that the standard dosage for pregnancy results in adequate therapeutic levels for antiretroviral suppression. 15,16 Administration of LPV/r oral liquid to pediatric patients results in a similarpharmacokineticprofiletothatobservedin adults.…”
Section: Mechanism Of Action Metabolism and Pharmacokinetic Profilementioning
confidence: 99%